Environmental barriers to reintegration experienced by stroke clients post discharge from a rehabilitation centre in Malawi - G. Chimatiro; A. Rhoda (AOSIS, 2014)
Although stroke clients undergo rehabilitation in minimise the impact of stroke on their functioning, they still experience challenge with reintegration.